Toward anticancer gold-based compounds targeting PARP-1: a new case study. Issue 82 (19th August 2016) - Citta, A.; Scalcon, V.; Göbel, P.; Bertrand, B.; Wenzel, M.; Folda, A.; Rigobello, M. P.; Meggers, E.; Casini, A.
Abstract : A new gold(iii ) complex bearing a 2-((2, 2′-bipyridin)-5-yl)-1 H -benzimidazol-4-carboxamide ligand has been synthesized and characterized for its biological properties in vitro . Abstract : A new gold(iii ) complex bearing a 2-((2, 2′-bipyridin)-5-yl)-1 H -benzimidazol-4-carboxamide ligand has been synthesized and characterized for its biological properties in vitro . In addition to showing promising antiproliferative effects against human cancer cells, the compound potently and selectively inhibits the zinc finger protein PARP-1, with respect to the seleno-enzyme thioredoxin reductase. The results hold promise for the design of novel gold-based anticancer agents disrupting PARP-1 function and to be used in combination therapies.